Clinical symptoms and signs for the diagnosis of Mycoplasma pneumoniae in children and adolescents with community‐acquired pneumonia - Wang, K; Gill, P; Perera, R; Thomson, A; Mant, D; Harnden, A (Wiley, 2012)
Background: Mycoplasma pneumoniae (M. pneumoniae) is a significant cause of community‐acquired pneumonia in children and adolescents. Treatment with macrolide antibiotics is recommended. However, M. pneumoniae is difficult to diagnose based on clinical symptoms and signs. Diagnostic uncertainty can lead to inappropriate antibiotic prescribing, which may worsen clinical prognosis and increase antibiotic resistance. Objectives: The objectives of this review are (i) to assess the diagnostic accuracy of symptoms and signs in the clinical recognition of M. pneumoniae in children and adolescents with community‐acquired pneumonia; and (ii) to assess the influence of potential sources of heterogeneity on the diagnostic accuracy of symptoms and signs in the clinical recognition of M. pneumoniae. Search methods: We searched MEDLINE (January 1950 to 26 June 2012) and EMBASE (January 1980 to 26 June 2012). We identified additional references by handsearching the reference lists of included articles and snowballing. We searched the reference lists of relevant systematic reviews identified by searching the Medion database, Database of Reviews of Effects 2012, Issue 6 (25 June 2012) and the Cochrane Register of Diagnostic Test Accuracy studies (2 July 2012). Experts in the field reviewed our list of included studies for any obvious omissions. Selection criteria: We included peer‐reviewed published studies which prospectively and consecutively recruited children with community‐acquired pneumonia from any healthcare setting, confirmed the presence of M. pneumoniae using serology with or without other laboratory methods and reported data on clinical symptoms and signs in sufficient detail to construct 2 x 2 tables. Data collection and analysis: One review author scanned titles to exclude obviously irrelevant articles. Two review authors independently scanned the remaining titles and abstracts, reviewed full‐text versions of potentially relevant articles, assessed the quality of included articles and extracted data on study characteristics and the following clinical features: cough, wheeze, coryza, crepitations, fever, rhonchi, shortness of breath, chest pain, diarrhea, myalgia and headache. We calculated study‐specific values for sensitivity, specificity and positive and negative likelihood ratios with 95% confidence intervals (CIs). We estimated the post‐test probability of M. pneumoniae based on the absence or presence of symptoms and signs. We calculated pooled sensitivities, specificities, positive and negative likelihood ratios with 95% CIs for symptoms and signs where data were reported by at least four included studies by fitting a bivariate normal model for the logit transforms of sensitivity and specificity. We explored potential sources of heterogeneity by fitting bivariate models with covariates using multi‐level mixed‐effects logistic regression. We performed sensitivity analyses excluding data from studies for which we were concerned about the representativeness of the study population and/or the acceptability of the reference standard. Main results: Our search identified 8299 articles (excluding duplicates). We examined the titles and abstracts of 1125 articles and the full‐text versions of 97 articles. We included seven studies in our review, which reported data from 1491 children; all were conducted in hospital settings. Overall, study quality was moderate. In two studies the presence of chest pain more than doubled the probability of M. pneumoniae. Wheeze was 12% more likely to be absent in children with M. pneumoniae (pooled positive likelihood ratio (LR+) 0.76, 95% CI 0.60 to 0.97; pooled negative likelihood ratio (LR‐) 1.12, 95% CI 1.02 to 1.23). Our sensitivity analysis showed that the presence of crepitations was associated with M. pneumoniae, but this finding was of borderline statistical significance (pooled LR+ 1.10, 95% CI 0.99 to 1.23; pooled LR‐ 0.66, 95% CI 0.46 to 0.96). Authors' conclusions: M. pneumoniae cannot be reliably diagnosed in children and adolescents with community‐acquired pneumonia based on clinical symptoms and signs. Although the absence of wheeze is a statistically significant diagnostic indicator, it does not have sufficient diagnostic value to guide empirical macrolide treatment. Data from two studies suggest that the presence of chest pain more than doubles the probability of M. pneumoniae. However, further research is needed to substantiate this finding. More high quality large‐scale studies in primary care settings are needed to help develop prediction rules based on epidemiological data as well as clinical and baseline patient characteristics.